Effect of Method Reciprocal Learning, Student Learning Interest on Learning Outcomes Construction Management - Aprianus Telaumbanua (Universitas Muhammadiyah Enrekang, 2022)
This study aimed to examine the effect of learning methods and learning interest on learning outcomes in construction management courses. Conducted research in the Building Engineering Education study program at Nias University. This research method is an experimental method with a 2x2 treatment by level design. Data analysis techniques using (anava) two paths, then continued with the Tuckey test. The results of the study are (1). there are differences in learning outcomes between students who use reciprocal learning methods and students who use discussion learning methods; (2). there is an interaction between learning methods and student learning interests; (3). the learning outcomes of students who use reciprocal learning methods are higher than those who use discussion learning methods in students with high learning interests; (5). the learning outcomes of students who use reciprocal learning methods are lower than those who use discussion learning methods in students with low learning interests.